Perezhivanie and Its Application within Early Childhood Science Education Research - Nikolaos Christodoulakis; Clara Vidal Carulla; Karina Adbo (MDPI AG, 2021)
Perezhivanie is a concept that was originally defined by Vygotsky, but it did not become a part of educational theory until recently. Today the concept has been revived, and it is now used as a way to include emotional aspects into education and educational research. The concept also provides a rationale for describing and forming personalised learning. The present study provides a literature review with the aim of covering the variety in definitions of the concept, as well as the different perspectives that the concept lends to research in general, and to research with focus on early years education in particular. Results show that the concept has been applied within the most common theoretical perspectives in use today (such as social, cultural and subjective perspectives) with an interesting array of outcomes, such as design of educational methods, analysis of different modes of experiencing and development of self-awareness. The use of this concept becomes a shift toward more emotional perspectives of learning and development that may not be altogether positive, as perezhivanie holds the risk of blurring the border between psychotherapy and education, which is something that would provide new challenges for education in general and especially for teacher education.